Microstructure Evolution Mechanism and Fracture Characteristic of Bimodal Size SiCp/Mg Composite - Mingjie Shen; Jiahong Jia (IEEE Access, 2019)
In this paper, as-extruded (~1μm + ~60 nm) bimodal size SiC particle (SiCp) reinforced magnesium matrix composite was subjected to step-by-step tensile treatment. The microstructure evolution and fracture characteristic of the composites were investigated. The experimental results indicated that the dislocations were accumulated mainly around the particles. Meanwhile, dislocation density increased with the strain increasing from 0% to 2.6% and hence, improved the tensile strength of the composite. According to the observation of the fracture process for the composites, the twinning was observed (away from the ~1μm SiCp). The dominant microcrack nucleation easily occurred at the interface between ~1μm SiCp(α-SiCp) and Mg matrix due to the stress concentration (which was caused by large size particle and the polygonal morphology). However, a good interface bonding between nano SiCp (β-SiCp) and matrix was indicated, and no microcracks were initiated around β-SiCp. The fracture features of the composite show that the existence of β-SiCp is helpful to improve the tensile properties, which is explained by the mechanisms such as the crack-propagation, obstruction, and crack blunting.